Disruption of the cyclic AMP phosphodiesterase-4 (PDE4)-HSP20 complex attenuates the β-agonist induced hypertrophic response in cardiac myocytes. - Sin, Y; Edwards, H; Li, X; Day, J; Christian, F; Dunlop, A; Adams, DR; Zaccolo, M; Houslay, MD; Baillie, G (2011)
The small heat shock protein HSP20 is known to be cardioprotective during times of stress and the mechanism underlying its protective abilities depends on its phosphorylation on Ser16 by PKA (protein kinase A). Although the external stimuli that trigger Ser16 phosphorylation have been well studied, the events that modulate spatial and temporal control of this modification remain to be clarified. Here, we report that inhibition of cAMP phosphodiesterase-4 (PDE4) induces the phosphorylation of HSP20 in resting cardiac myocytes and augments its phosphorylation by PKA following β-adrenergic stimulation. Moreover, using peptide array technology, in vitro binding studies, co-immunoprecipitation techniques and immunocytochemistry, we show that HSP20 binds directly to PDE4 within a region of the conserved catalytic domain. We also show that FRET-based, genetically-encoded cAMP reporters anchored to HSP20 exhibit a larger response to PDE4 inhibition compared to free cytosolic cAMP reporters, suggesting that the interaction with PDE4 is crucial in modulating the highly localised pool of cAMP to which HSP20 is exposed. Using information gleaned from peptide array analyses, we developed a cell-permeable peptide that serves to inhibit the interaction of PDE4 with HSP20. Disruption of the HSP20-PDE4 complex, using this peptide, suffices to induce phosphorylation of HSP20 by PKA and to protect against the hypertrophic response measured in neonatal cardiac myocytes following chronic β-adrenergic stimulation.